Ecological safety of the region`s population in the aspect of the logistic-activity approach to its formation and legal regulation - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Кузьминчук, Наталія Валеріївна; Кузьминчук, Н. В.; Кузьминчук, Наталия Валерьевна; Kuzmynchuk, Nataliia V.; Тарасенко, Вікторія Сергіївна; Тарасенко, В. С.; Тарасенко, Виктория Сергеевна; Tarasenko, Viktoriia S.; et al. (IOP Publishing, 2021)
The issues of ensuring the ecological safety of the region`s population are actualized in the context of the growth increasing in the natural resources, accompanied by the increase in anthropogenic pressures on the environment and humans, aggravation of environmental problems, deterioration of the life quality and environmental conditions of activity in the region. The aim of the study is to develop the theoretical foundations for ensuring the ecological safety of the population of the region on the basis of a logistic-activity approach to its formation in the context of legal regulation of the environmental management process as a factor in achieving sustainable development goals and increasing energy efficiency. Using the methods of economic and mathematical modeling it is substantiated the existence of the relationship between the level of ecological safety of the region's population and the amount of the funds from the budget allocated to finance environmental programs. Improving the legal regulation of the processes of ensuring the ecological safety of the region's population for optimizing the budget expenditures for the implementation of environmental programs will create the conditions for realizing the economic potential of the region's development, increasing the level and quality of life of the population.

Питання забезпечення екологічної безпеки населення регіону актуалізуються в умовах приросту природних ресурсів, що супроводжується збільшенням антропогенного навантаження на навколишнє середовище та людину, загостренням екологічних проблем, погіршенням якості життя. та екологічні умови діяльності в регіоні. Метою дослідження є розробка теоретичних основ для забезпечення екологічної безпеки населення регіону на основі логістично-діяльнісного підходу до її формування в контексті правового регулювання процесу природокористування як чинника досягнення цілей сталого розвитку та підвищення енергоефективності. За допомогою методів економіко-математичного моделювання обґрунтовано наявність взаємозв’язку між рівнем екологічної безпеки населення регіону та обсягом бюджетних коштів, спрямованих на фінансування екологічних програм. Удосконалення правового регулювання процесів забезпечення екологічної безпеки населення регіону для оптимізації видатків бюджету на реалізацію екологічних програм створить умови для реалізації економічного потенціалу розвитку регіону, підвищення рівня та якості життя населення регіону.
Kuzmynchuk N. Ecological safety of the region`s population in the aspect of the logistic-activity approach to its formation and legal regulation / N. Kuzmynchuk, S. Kivalov, V. Tarasenko, S. Voloshyna, R. Chanyshev, O. Shchukin // IOP Conf. Series: Earth and Environmental Science 915(2021) 012027. - IOP Publishing, 2021. - 7 p.
Keywords: ecological safety of the region; legal regulation of the environmental management process; environmental programs; optimizing the budget expenditures; екологічна безпека регіону; правове регулювання процесу природокористування; екологічні програми; оптимізація видатків бюджету; Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law